Transforming the Medical Subject Headings into Linked Data: Creating the Authorized Version of MeSH in RDF - Bushman, Barbara (J Libr Metadata, 2016)
In February 2014 the National Library of Medicine formed the Linked Data Infrastructure Working Group to investigate the potential for publishing linked data, determine best practices for publishing linked data, and prioritize linked data projects, beginning with transforming the Medical Subject Headings as a linked data pilot. This article will review the pilot project to convert the Medical Subject Headings from XML to RDF. It will discuss the collaborative process, the technical and organizational issues tackled, and the future of linked data at the library.